Pengembangan Karakter Dan Keterampilan Peserta Didik Melalui Kegiatan Ekstrakurikuler Di SDN 244 Guruminda Dan SD Plus Al-Ghifari - Chairunnisa Chairunnisa; Defany Dwi Rahmadhani; Nabila Ratri Widya Astuti; Syifaun Nafisah (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to find out how extracurricular activities carried out at SDN 244 Guruminda and SD Plus Al Ghifari can help develop students' character and skills. The research used a descriptive analysis method with the research subjects being the deputy head of the school in the field of curriculum and students. Data collection techniques by conducting interviews and observing extracurricular activities at school. As a result, extracurricular activities at school are able to have a good impact on students in the form of developing students' character and skills. Extracurricular activities carried out outside the classroom provide a variety of learning that is not only fixed in the classroom. Extracurricular activities provide learning experiences outside the classroom for students to become independent human beings, able to work together, able to solve problems, be creative, and always behave well. Therefore, schools as educational units should always carry out extracurricular development activities in order to create students who have good character as a provision to more easily survive life in the future.